A preliminary survey of Muslim experts’ views on artificial intelligence - Aliff Nawi,; Mohd Faiz Mohd Yaakob,; Chua, Chy Ren; Nor Yazi Khamis,; Ab Halim Tamuri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
There should be a great deal of concern over the extensive and still expanding application of artificial intelligence (AI) technology in Muslim life today. From the use of smartphones, drones, robots, autonomous vehicles and weapons technologies, the transformation caused by AI is significantly positive but much is still up for debate and contemplation. In fact, some Muslims may merely consider this rapid growth of AI as part of science fiction which is being popularised in movies. This incognizant view is dangerous because Muslims may not be alert to unforeseen AI impact especially when it crosses over Islamic ethical or legal limits. These interpretations should provide an appropriate context for Muslim experts today to rethink their views with regards to the transformative impact of AI on Muslim society. This preliminary study therefore, is conducted to gather Muslim experts’ professional views on AI related issues. Using a quantitative methodology approach with a cross-sectional study design, 37 experts responded to the personal, online questionnaire emailed to them. The findings generally indicate the respondents’ insensitivity towards the greater extent of AI impact on Muslim consumers at large. However, most of the respondents were agreeable on the urgent need for regulations so that AI is geared and harvested for its benefits in enhancing Muslim life. This signifies the importance of thorough and strict regulations for AI research and technology to adhere to Islamic principles. A specific framework development underpinned by Maqasid al-Shari’ah is recommended to address the various contemporary issues of AI impact.